Telebasis vulcanoae (Machado, 1980) (Odonata: Coenagrionidae): discovery of a population in Northeastern Brazil and potential distribution in South America - Farias, Antonio B. S.; Gomes, Thiago C.; Venâncio, Henrique; Santos, Jean C. (Entomological Communications, 2026)
In this study, we report the first record of Telebasis vulcanoae (Machado 1980) in the state of Sergipe, Northeastern Brazil, expanding its known distribution previously restricted to Minas Gerais and Bahia. Specimens were collected on the campus of the Federal University of Sergipe in areas with temporary rainwater pools and small semi-deciduous forest fragments. We also investigated the potential distribution of species in South America using a niche modelling procedure that adopted the described occurrence records and bioclimatic variables. Eighteen specimens (10 females and eight males) were sampled. Niche modelling revealed that T. vulcanoae has high environmental suitability in the northern and central-western regions of Brazil, mainly in coastal and forested areas. Our study contributes to future research on the conservation status of T. vulcanoae, which is currently classified as Data Deficient in the IUCN Threatened Species List.